OUTCOME OF MODIFIED STOPPA TECHNIQUE FOR THE MANAGEMENT OF ACETABULAR FRACTURES - Muhammad Saeed,; Abdul Sattar,; Muhammad Inam,; Zeeshan Khan,; Shafi Ul Haq, (Journal of Ayub Medical College Abbottabad, 2026)
Objective: To evaluate outcome in terms of radiological and clinical outcome of modified Stoppa technique for the management of acetabular fractures. Methodology: This descriptive study was conducted at Orthopedic & Spine Unit, Hayatabad Medical Complex, Peshawar from January 2023 to January 2024. Fifty three patients with acetabular fractures were managed with modified Stoppa technique. Outcome such as radiological and clinical were assessed after 8 months of the procedure. Numerical data was assessed with mean and standard deviation while categorical with frequency and percentage. Chi Square test was used for association keeping P value significant at < 0.05. Results: The mean age of participants was 44.62±11.69 years, with higher frequency of male patients. The mean operative time recorded was approximately 155.45±34.28 minutes, and the mean blood loss was 741.43±107.28 ml. Anatomical reduction was achieved in 39 (73.6%) of cases on the basis of Matta's criteria for radiological assessment, while clinical outcome were rated as excellent in 16 (30.2%) patients, good 29 (54.7%) patients, fair 6 (11.3%) patients while poor in 2 (3.8%) on the basis of Harris Hip Score. Conclusion: Modified Stoppa Approach is a safe and potent procedure for the management of acetabular fractures exhibiting radiological and clinical outcome up to the mark. Keywords: Acetabular fractures, Modified Stoppa Approach, Radiological outcome, Clinical outcome